Three holidays and a wedding - Jalaluddin, Uzma; Stapley, Marissa (G. P. Putnam's Sons, 2023)
"As strangers and seatmates Maryam Aziz and Anna Gibson fly to Toronto over the holidays--Maryam to her sister's impromptu wedding, and Anna to meet her boyfriend's wealthy family for the first time--neither expect that severe turbulence will scare them into confessing their deepest hopes and fears to one another. At least they'll never see each other again. And the love of Maryam's life, Saif, wasn't sitting two rows behind them hearing it all. Oops. An emergency landing finds Anna, Saif, Maryam, and her sister's entire bridal party snowbound at the quirky Snow Falls Inn in a picture-perfect town, where fate has Anna's actor-crush filming a holiday romance. As Maryam finds the courage to open her heart to Saif, and Anna feels the magic of being snowbound with an unexpected new love--both women soon realize there's no place they'd rather be for the holidays."--